Investigating the working efficiency of natural wastewater treatment systems: A step towards sustainable systems - Ramdas Pinninti (IWA Publishing, 2021)
Globally, wastewater is a vital resource and requires appropriate treatment management strategies. Wastewater has become a major source of irrigation in the peri-urban areas of developing nations. With the increasing amount of wastewater generation, there are several complications in using treatment systems in terms of installation, operation and maintenance, and size in developing countries. Recently, natural treatment systems are gaining popularity due to less cost and maintenance and have been preferred in peri-urban settings. In this study, the working efficiency of the natural systems was assessed from case studies from Vizianagaram, Andhra Pradesh, India. The nutrient (Phosphorus and Nitrogen content) and organic matter removal efficiency of four natural treatment systems (NTS) having different operation, maintenance and loading rates were investigated. The study showed that natural treatment systems have good potential for peri-urban wastewater treatment. It was also observed that waste-stabilization based systems perform better than those based on duckweed and hyacinth plants. Regularly maintained and operated systems show removal efficiency on the order of 80% for organic and nutrients and performed better than others. The study indicates that decentralized, adequately maintained waste stabilization ponds (WSP) offer a viable, self-sustaining and eco-friendly alternative for wastewater treatment to supply irrigation water in rural areas. Highlights Working efficiency of natural treatment systems (NTS) in wastewater treatment.; The results evidently support the NTS as a viable and sustainable alternative for peri-urban and even urban areas for effective treatment of domestic wastewater.; This study bring awareness to farmers, stakeholders and policymakers about the working mechanism and significance of these systems and thereby their involvement in the maintenance.;